Development of a remote teleoperation interface for robotic wheelchair navigation - Selvam Vinothini Vibhusha (Nanyang Technological University, 2024)
Robotic wheelchairs empower individuals with impaired motor skills to navigate their surroundings independently, enhancing their autonomy and quality of life. However, traditional control interfaces for robotic wheelchairs often pose challenges, particularly for users with reduced fine motor skills. In such situations, caregivers can assist the wheelchair user. However, caregivers cannot help the wheelchair users navigate at all times because of other commitments. Therefore, this final-year project proposes a novel teleoperation interface. The teleoperation interface allows caregivers remote access to the wheelchair's navigation controls, providing guidance upon user request. The Intention Prediction Based Shared Control algorithm developed by the Rehabilitation Research Institute of Singapore, enhances safety during wheelchair navigation. It overrides imprecise user input to the joystick that can result in potential collision. This algorithm is integrated into the teleoperation interface to improve the safety of the wheelchair user. Prior to interface design, extensive evaluation of existing interfaces and teleoperation systems is conducted to identify key design features for intuitive usability. Leveraging web technologies and ROS (Robot Operating System), the teleoperation interface is developed to facilitate seamless interaction between the teleoperator and wheelchair. The system’s efficacy is validated through both simulated and real-world experiments using the Rehabilitation Research Institute's robotic wheelchair. The benefits of Shared Control for teleoperation tasks is also evaluated.